1996
DOI: 10.1001/archsurg.1996.01430130100022
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Conversion of Laparoscopic Cholecystectomy to Open Surgery

Abstract: Risk factors, including patient factors, presentation, preoperative ultrasonography, and surgical experience, all contributed to the possibility of conversion. Knowledge of these factors may help in arranging the operating schedule, psychological preparation for the procedure, and planning of the duration of convalescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
99
3
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 11 publications
12
99
3
6
Order By: Relevance
“…Similar results has been concluded in other studies. 6,9 In the study 63.16% patients in converted group had TLC more than 11000. Ibrahime et al and Bediril et al showed similar results.…”
Section: Resultsmentioning
confidence: 82%
“…Similar results has been concluded in other studies. 6,9 In the study 63.16% patients in converted group had TLC more than 11000. Ibrahime et al and Bediril et al showed similar results.…”
Section: Resultsmentioning
confidence: 82%
“…19 Schrenk P et al in their study have mentioned previous abdominal surgery as a risk factor predicting difficult laparoscopic cholecystectomy and higher conversion rates. 20 Michael Rosen, Fred Brody, Jeffrey Ponsky found in their series that obesity independently predicted conversion to open cholecystectomy in patients with acute cholecystitis. 21 Simopon'os et al in their study had found diabetes as a predictor of difficult laparoscopic cholecystectomy.…”
mentioning
confidence: 99%
“…Advancing age was found to be a risk factor for conversion in our study (p <0.05). [1][2][3][9][10][11] Patients who had multiple attacks of acute cholecystitis (more than one) had higher chances of difficult laparoscopic cholecystectomy and conversion, probably due to dense adhesions at calot's triangle and gall bladder fossa. This was supported by Gupta N et al, Nidoni R et al, Randhawa JS et al, Ali Rizvi et al and others.…”
Section: Discussionmentioning
confidence: 99%